NEUROTHERAPEUTIC EFFECT OF MANGIFERIN AGAINST HYPOXIC–ISCHEMIC ENCEPHALOPATHY IN NEONATAL RATS - Lv, Xiu-li; Wang, Yi; Hu, Bing; Kang, Le; Xin, Jun; Zhang, Guo-Ying (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Hypoxic–ischemic encephalopathy (HIE) in perinatal condition is highly associated with mortality and several neurological disabilities. The present experiment was blueprinted to ascertain the protective efficacy of mangiferin (MF) against hypoxic–ischemic brain injury in neonatal rats. Materials and methods: Fourth six neonatal rats (pubs) were arbitrarily separated into four groups as a sham group that received only water (control; n=12), pubs exposed to Hypoxic–ischemic (HI) insult (HI group-II; n=11), pubs receiving 20 (MF 20+HI-III; n=11) or 40 (MF 40+HI-IV; n=12) mg/kg b. wt of MF dissolved in water via i.p. for 7 consecutive days as pretreatment regimen before HI insult. Results: MF pretreatment for seven days considerably attenuated the cerebral infarct size, edema level, lipid peroxidation (MDA), inflammatory markers (TNF-α, IL-1β, IL-6, and NF-p65 subunit) as well as greatly ameliorated the antioxidant activities of catalase (CAT), superoxide dismutase (SOD), and glutathione reductase (GSH) and thereby maintaining the redox balance. The number of viable neuronal count (nissl bodies) was exponentially increased on administration with both the dosages of MF. Both the dosages showed substantial protection against HIE, however, 40 mg of MF exhibit superior neuroprotection in equivalence with 20 mg of MF. Conclusion: The outcome of the present study distinctly proving the beneficial effect of MF against HIE by concomitantly improving neuronal count and antioxidant status. Hence, we recommend MF might be used for treating neonatal HIE with some standard drugs. Keywords: Hypoxic–ischemic encephalopathy, Mangiferin, Antioxidant, Inflammation, Neuroprotective